Development of stretch-shortening cycle function in girls during maturation and in response to training: a narrative review - McGarrigal, L. D.; Morse, C. I.; Sims, D. T.; Stebbings, G. K. (The Journal of Strength and Conditioning Research, 2025)
The aim of this narrative review was to examine stretch-shortening cycle (SSC) function and to explore its effects on the athletic performance in girls during maturation and in response to plyometric training (PT), where there has been limited focus to date. The SSC is an integral component of explosive actions such as sprinting and jumping. Literature shows that the SSC develops during maturation because of several morphological, neurophysiological, and structural mechanisms, and that the SSC response can be amplified by training. Research suggests that boys experience "accelerated adaptation" in slow and fast SSC function as they mature, but to date, similar studies in girls are limited and often contradictory. Plyometric training capitalizes on the ability of the SSC to generate greater force production by including an eccentric muscle action quickly followed by a concentric action. However, the number of PT studies involving youth female athletes is lacking, with only 10% of all PT studies including female subjects aged <18 years. This is surprising given that PT can enhance athletic performance and reduce the risk of noncontact anterior cruciate ligament injuries in girls. After PT, boys experience "synergistic adaptation," which is the symbiotic relationship between PT strategically programmed to coincide with the development of the SSC that is being concurrently enhanced by the processes of growth and maturation. Establishing if girls experience periods of accelerated and synergistic adaptation in slow and fast SSC function after PT would likely influence future training in this population, which has traditionally been underserved.